Quem cabe nos concursos públicos?: o processo de tradução de provas de concursos públicos da área jurídica do português para a Libras - um olhar do dialogismo e da ciência aberta - Assis, Amanda (2024)
This research is part of the institutional proposal "Multimodal/Multilingual Portal for the Advancement of Open Science in the Humanities," aimed at establishing a segment focused on the productions of Translators and Interpreters of Brazilian Sign Language (Libras)-Portuguese/Portuguese-Libras (TILS). Recognizing the multimodality of the translation process involving vocal/written language and signed language, as well as the tense discursive interaction represented by the selective exam situation, we seek to understand the Libras translator role in civil service examinations, translating from written Portuguese to Libras through their discourses about their practice. We focus on professionals experienced primarily in exams granting access to the judiciary. The corpus comprises the transcription of four semi-structured interviews with translators selected from a convenience sample regarding their professional practice in translating civil service examinations, analyzed using the methodology developed by Campos (2007). The theoretical foundation is based on Dialogical Discourse Analysis, associated with other knowledge strands, such as official documents and constitutional principles governing civil service examinations, as well as Translation Studies. As a result of scientific relevance and social impact, we propose recommendations for action: exam translation, which may compose translators training